Prevention of Latent Safety Threats: A Quality Improvement Project to Mobilize a Portable CT. Issue 4 (23rd July 2021) - Lawrence, Julia F.; Tsang, Rocky; Fedee, George; Musick, Matthew A.; Lichliter, Royanne L.; Bastero, Patricia; Pedroza McDonald, Nadia; Wallin, Kelly; Doughty, Cara
Abstract : Introduction: Transporting critically ill patients to diagnostic imaging for needed studies can be challenging and even prohibitive. A portable computerized tomography (CT) scanner allows the patient to remain in the intensive care unit, but presents new positioning and team challenges. Before activation of a portable CT scanner in our pediatric intensive care unit and through the use of iterative simulation-based Plan-Do-Study-Act (PDSA) cycles in the clinical environment, a multidisciplinary team of bedside caregivers determined optimal patient positioning, equipment needs, and specific staffing and choreography to develop detailed portable CT guidelines. Method: Our team engaged stakeholders from radiology, critical care, respiratory therapy, environmental services, facilities operations, and the CT vendor to develop scenarios. Simulations included infant and pediatric patients who required critical invasive monitoring and treatment devices, such as ventilators, and high-risk intracardiac and intravascular lines. Scenario objectives centered on the safe positioning, transfer, and scanning of the patient. Trained simulation specialists from the hospital's simulation center facilitated simulation sessions. Results: Simulation-based PDSA testing identified 31 latent safety threats, including the need for a custom bed adapter due to pediatric patients' variable size. We paused portable CT activation pending the custom adapter's availability and remediation of other latent safety threats. Additional simulation-based PDSA cycles further refined the process once the custom adapter was available. Conclusions: Simulation identified unanticipated latent safety threats before the implementation of a portable CT scanner.